Foreign consumer perception of tourism services - Yahya, Salleh (Universiti Putra Malaysia Press, 2000)
This paper performs an assessment of tourists' perception towards services associated with lodging (hotel factors), dining (restaurant factors), and transportation (transportation factors). The results of the empirical analysis suggested that these are the underlying dimensions held by the tourists: (1) Hotel factors - Staff service quality, room quality, business services,. security, value and food quality, and general amenities, (2) Restaurant factors - serving and food quality, accessibility, and general service and layout design, and (3) Transportation factors: system quality, accessibility, and staff service quality. By linking these factors with tourists' overall satisfaction level, those factors that significantly contribute to better traveling satisfaction have been identified. In addition, this paper provides information on level of service performance, and sheds light on areas that present great potential in retaining and attracting tourists.